Processing and Subcellular Localization of the Hepatitis E Virus Replicase: Identification of Candidate Viral Factories - Metzger, Karoline; Bentaleb, Cyrine; Hervouet, Kévin; Alexandre, Virginie; Montpellier, Claire; Saliou, Jean-Michel; Ferrié, Martin; Camuzet, Charline; Rouillé, Yves; Lecoeur, Cécile; Dubuisson, Jean; Cocquerel, Laurence; et al. (Frontiers in Microbiology, 2022)
Hepatitis E virus (HEV) is the major cause of acute hepatitis worldwide. HEV is a positive-sense RNA virus expressing 3 open reading frames (ORFs). ORF1 encodes the ORF1 non–structural polyprotein, the viral replicase which transcribes the full-length genome and a subgenomic RNA that encodes the structural ORF2 and ORF3 proteins. The present study is focused on the replication step with the aim to determine whether the ORF1 polyprotein is processed during the HEV lifecycle and to identify where the replication takes place inside the host cell. As no commercial antibody recognizes ORF1 in HEV-replicating cells, we aimed at inserting epitope tags within the ORF1 protein without impacting the virus replication efficacy. Two insertion sites located in the hypervariable region were thus selected to tolerate the V5 epitope while preserving HEV replication efficacy. Once integrated into the infectious full-length Kernow C-1 p6 strain, the V5 epitopes did neither impact the replication of genomic nor the production of subgenomic RNA. Also, the V5-tagged viral particles remained as infectious as the wildtype particles to Huh-7.5 cells. Next, the expression pattern of the V5-tagged ORF1 was compared in heterologous expression and replicative HEV systems. A high molecular weight protein (180 kDa) that was expressed in all 3 systems and that likely corresponds to the unprocessed form of ORF1 was detected up to 25 days after electroporation in the p6 cell culture system. Additionally, less abundant products of lower molecular weights were detected in both in cytoplasmic and nuclear compartments. Concurrently, the V5-tagged ORF1 was localized by confocal microscopy inside the cell nucleus but also as compact perinuclear substructures in which ORF2 and ORF3 proteins were detected. Importantly, using in situ hybridization (RNAScope®), positive and negative-strand HEV RNAs were localized in the perinuclear substructures of HEV-producing cells. Finally, by simultaneous detection of HEV genomic RNAs and viral proteins in these substructures, we identified candidate HEV factories.